Assessing population diversity in phase III trials of cancer drugs supporting Food and Drug Administration approval in solid tumors. Issue 7 (5th July 2021) - Yekedüz, Emre; Trapani, Dario; Xu, Wenxin; de Vries, Elisabeth G. E.; Labaki, Chris; Gyawali, Bishal; Gulati, Shuchi; Nabhan, Chadi; Utkan, Güngör; Curigliano, Giuseppe; Choueiri, Toni K.; Ürün, Yüksel
Abstract: Our study aimed to assess inequities in the clinical trial participation for the selected patient groups. We searched the Food and Drug Administration (FDA) database and extracted phase‐III clinical trial data from MEDLINE for each approved drug by the FDA between January 1, 2006, and June 30, 2020. We analyzed the inclusion/exclusion criteria, participation according to gender, ethnic group, performance score, the positivity of HBV and HCV, and HIV, having comorbidities and brain metastasis. We compared the findings with that of the general population by retrieving data from the Surveillance, Epidemiology and End Results (SEER) database. We identified 142 phase III pivotal oncology trials that enrolled 105 397 patients. The proportion of female patients in trials was lower than their relative prevalence in the general population from SEER region (36% vs 49.6%, P  < .001). The rates of black patients included were lower than their relative prevalence from SEER region (2.1% vs 9.8%, P  < .001). 1.3% and 0.8% of patients had HBV and HCV infections, respectively. The patients' numbers with organ dysfunction were not established due to insufficient data from clinical trials. 1.6% of all patients had controlled brain metastasis. Black patients, women and patients with brain metastasis or with HBV and HCV were underrepresented. Our study underscores the importance of expanding the inclusion/exclusion criteria of pivotal oncology trials to be more representative of patients seen in clinical practice.